IMPLEMENTASI MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS I SD NEGERI 005 SIKAKAK - Amrin Amrin (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
The background of this research is the low learning outcomes of students in grade I SD Negeri 005 Sikakak, thisis caused by monotonous learning activities and does not involve student activities actively, so that studentsbecome saturated, bored and passive. To solve this problem, the researcher made efforts to improve learning byapplying picture media. This research is a classroom action research conducted at SD Negeri 005 Sikakak, thesubject of this research is class I students with 23 students. The data used in this study is the data of students'mathematics learning outcomes. The results showed that the learning outcomes experienced an increase in theinitial data average value obtained by students was 58.68 (less), increased in the first cycle to 69.24 (enough),and increased again in cycle II to 75.72 (good ) Based on the data acquisition, it can be concluded that theapplication of image media can improve the mathematics learning outcomes of grade I students of SD Negeri005 Sikakak.